I‘ādah Taḥdīd al-Qiblah fī Masjid al-Muhājirīn bi-Keirum – Bābūā min khilāl Ṭarīqatayn: al-Falakiyyah wa-al-Fiqhiyyah - Rahman, Hendra Yulia; Amri; Akbar, Taufiq (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
The Qibla direction constitutes a fundamental element in Islamic worship, particularly in the performance of prayer, as it is one of the essential conditions for its validity. However, the accuracy of the Qibla orientation in many mosques remains an issue that requires re-examination, including in Al-Muhajirin Mosque, Keerom, Papua. This study aims to analyze and reconstruct the Qibla orientation of the mosque by employing both astronomical and jurisprudential approaches. The falakiyyah approach involves field observation and measurement using Qibla-determining instruments such as the compass, theodolite, and Qibla applications. The fiqhiyyah analysis engages in a literature study of classical fiqh texts and relevant legal opinions (fatwas) concerning the importance of Qibla accuracy, complemented by interviews with local religious figures to capture communal perceptions of Qibla correction. The research adopts a field research design with a descriptive-qualitative approach, integrating both astronomical and juridical perspectives. The findings indicate a measurable deviation in the current Qibla orientation, necessitating correction to align with precise geographical coordinates. From a jurisprudential perspective, adjusting the Qibla becomes imperative in order to achieve the integrity of worship. Consequently, the reconstruction entails both positive and negative implications for the congregation of Al-Muhajirin Mosque.